Teknik Pengembangan Industri Ekotourisme Kota Batu Propinsi Jawa Timur Dalam Perspektif Kebijakan - Moch. Agus Krisno Budiyanto (Jurnal Teknik Industri, 2010)
From the previous researches, the typology development of Batu City ecotourism potency  (Budiyanto, 2006), ecotourism potency of Canggar (Budiyanto, 2005-a). Nevertheless, the technical for ecotourism development industries in Batu City based on policy perspective has not been explored further. For this reason, this research aims at finding the the development of Batu City ecotourism in policy perspective. To achieve this aim, the scopes of this research is the technical for ecotourism development industries in Batu City based on policy perspective. The design of research used in this research is qualitative research (fenomenologys). The subject is adalah Batu City Planing dan Development Office and Batu City Tourism Office. The data collection method used is documentation and interview. The data was analyzed qualitatively (Content Analysis) by means of interactive model from Miles and Huberman (Miles & Huberman, 1994). The result of the analysis was presented in the form of cross tabulation and the narration from the phenomena. From the research finding the technical for ecotourism development industries in Batu City bassed on policy perspective included The International Ecotoursm Society and Mader is good. Generaly The International Ecotourism Society and Mader indicator was development in policy perspective.